Teba Bebas Sampah: Partisipasi Masyarakat dalam Mewujudkan Desa Sulangai sebagai Kawasan Bebas Sampah - Ni Made Anggita Sastri Mahadewi; Gede Kamajaya; I Gusti Ngurah Agung Krisna Aditya (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
The habit of throwing garbage into the river that has been carried out for generations by the Balinese people, including in Sulangai Village, is currently no longer relevant. This is due to changes in the types of waste produced. If in the past most of the waste was organic and easily decomposed, now most of the waste that is thrown away consists of non-organic waste that is difficult to decompose, such as plastic and other synthetic materials. This practice is not in line with the government program that has designated Petang District as a pilot project for a waste-free area and the use of plastic bags. Based on the results of previous research in Sulangai Village, it was found that the behavior of throwing garbage into the river was influenced by two main factors: first, habits that have been carried out for generations; and second, the location of the temporary waste disposal site (TPS) which is too far from community organizations. To overcome this problem, this community service activity was carried out as an effort to reduce waste in the river area and encourage changes in community behavior. The activity began with an audience with the Sulangai Village government to build synergy. Furthermore, the provision and handover of carts to waste residents was carried out. Usually, with the availability of more accessible transportation facilities, residents can start throwing garbage into carts, which will then be collected and disposed of at TPS. Through this social service activity, it is hoped that a cleaner and healthier environment can be created, as well as being a stimulant for changes in residents' behavior in managing household waste more responsibly.